Need Analysis for Development (E-Module) of Analytical Chemistry Integrated with Environmental Analysis Research Results - Yulis, Putri Ade Rahma; Oktariani, Oktariani (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The current condition is still limited to analytical chemistry teaching materials that are integrated with research results, only using Analytical Chemistry textbooks as teaching materials or in the form of e-books. This is one of the causes of the lack of student interest in participating in the teaching and learning process. The purpose of this research is to produce innovative teaching materials in analytical chemistry based on research results, aiming to enhance students’ interest in learning.This research is the initial stage as a basis for developing analytical chemistry e-modules integrated with research results. The development model used is ADDIE which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. This research is limited to the needs analysis stage which includes RPS analysis, analysis of problems and needs of lecturers and problems and needs of students. Data collection instruments used interviews and questionnaires. The subjects of this study consisted of 6 Analytical Chemistry lecturers and 59 students from Riau Province, Riau Islands, North Sumatra, and West Java. The research results of this preliminary analysis include RPS analysis where there are 10 topics of study material and based on the needs questionnaire the topic of quantitative analysis is the topic with the highest percentage to be developed into an e-module. Then also obtained the results that there are still some shortcomings with the teaching materials used today, so that 98% of lecturers and students stated that they need the development of teaching materials, especially those that are digital-based and can be integrated with research results which are evidence of the implementation of analytical chemistry learning theory.Â